Orchid exploration in Mount Bintan Besar Protected Forest, Bintan Island, Riau Islands Province, Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2018)
Puspitaningtyas DM. 2018. Orchid exploration in Mount Bintan Besar Protected Forest, Bintan Island, Riau Islands Province, Sumatra, Indonesia. Biodiversitas 19: 1081-1088. Sumatra is one of the main islands in Indonesia. The biodiversity is higher than Java, but still below compare to Borneo and New Guinea. About 1,118 species of orchids are found growing in Sumatra, which 41% of these are endemic to Sumatra. The exploration activities were conducted at Gunung Bintan Besar Protected Forest, Bintan island-Sumatra. Orchid exploration was conducted in this area to collect living plants for ex situ conservation purpose. Orchid inventory to record orchid diversity in this area, based on plant collection by purposive random sampling. The results of the study recorded approximately 23 orchid collection numbers found in that area. These were representative of 15 genera and consist of 14 species of epiphyte orchids and 9 species of terrestrial orchids. Most orchids found in this area are lowland orchid which are very common in Sumatra. Dendrobium metachilinum Rchb.f., Dendrobium leonis (Lindl.) Rchb.f. and Plocoglottis lowii Rchb.f. are unique orchids species found on this island.
Keywords: Bintan Island; exploration; inventory; orchid